Bacterial chemotaxis in static gradients quantified in a biopolymer membrane-integrated microfluidic platform. Issue 17 (20th July 2022) - Hu, Piao; Ly, Khanh L.; Pham, Le P. H.; Pottash, Alex E.; Sheridan, Kathleen; Wu, Hsuan-Chen; Tsao, Chen-Yu; Quan, David; Bentley, William E.; Rubloff, Gary W.; Sintim, Herman O.; Luo, Xiaolong
Abstract : Adhesion-free bacterial chemotaxis was quantified in static gradients in a wide 2D area generated in a biopolymer membrane-integrated microfluidic platform. Abstract : Chemotaxis is a fundamental bacterial response mechanism to changes in chemical gradients of specific molecules known as chemoattractant or chemorepellent. The advancement of biological platforms for bacterial chemotaxis research is of significant interest for a wide range of biological and environmental studies. Many microfluidic devices have been developed for its study, but challenges still remain that can obscure analysis. For example, cell migration can be compromised by flow-induced shear stress, and bacterial motility can be impaired by nonspecific cell adhesion to microchannels. Also, devices can be complicated, expensive, and hard to assemble. We address these issues with a three-channel microfluidic platform integrated with natural biopolymer membranes that are assembled in situ . This provides several unique attributes. First, a static, steady and robust chemoattractant gradient was generated and maintained. Second, because the assembly incorporates assembly pillars, the assembled membrane arrays connecting nearby pillars can be created longer than the viewing window, enabling a wide 2D area for study. Third, the in situ assembled biopolymer membranes minimize pressure and/or chemiosmotic gradients that could induce flow and obscure chemotaxis study. Finally, nonspecific cell adhesion is avoided by priming the polydimethylsiloxane (PDMS) microchannel surfaces with Pluronic F-127. We demonstrated chemotactic migration of Escherichia coli as well as Pseudomonas aeruginosa under well-controlled easy-to-assemble glucose gradients. We characterized motility using the chemotaxis partition coefficient (CPC) and chemotaxis migration coefficient (CMC) and found our results consistent with other reports. Further, random walk trajectories of individual cells in simple bright field images were conveniently tracked and presented in rose plots. Velocities were calculated, again in agreement with previous literature. We believe the biopolymer membrane-integrated platform represents a facile and convenient system for robust quantitative assessment of cellular motility in response to various chemical cues.